Use of Used Goods as A Media for Developing Fine Arts Creativity for Students of Primary School Negeri 1 Mayongkidul - Assakhiy, Herfiana Putri; Wijayanto, Wasis (Jurnal Prajaiswara, 2024)
Introduction/Main Objectives: The decline in elementary school students' creativity is increasingly visible, where nowadays they prefer to play with gadgets rather than create works of art, besides that many of them don't care about the surrounding environment, so this article aims to describe efforts to develop students' creativity through the use of used goods that are available. around where he lives. Research Methods: The research method used in this article is qualitative descriptive research, using 2 data sources, namely, primary data and secondary data, primary data was obtained from observation, interviews and documentation. Meanwhile, secondary data was obtained from journal articles and other supporting data. Finding/Results: Researchers hope that this research will be able to show that the use of used goods can develop the fine arts creativity of students at SD Negeri 1 Mayongkidul.